HEALTH EDUCATION IN EMPOWERING HEALTHY YOUTH TO INCREASE KNOWLEDGE ABOUT EARLY MARRIAGE AT MTS NURUL HUDA - Ardhiani, Innas; Kusuma, Ratih; Mardiana, Heppy (Jurnal Layanan Masyarakat (Journal of Public Services), 2024)
Adolescents experience a period of rapid growth and development both physically, psychologically and intellectually. Based on the results of the evaluation of the Integrated Gempar activities in Petungsewu Village in 2022, there are 24% of teenagers who get married early. So it is necessary to provide preventative efforts to provide health education in schools. This method is able to increase adolescent knowledge and change adolescent behavior to improve their health status independently. Community service activities were carried out on Wednesday, October 11 202 at 10.00 – 12.00 at MTs Nurul Huda, Petungsewu Village, Dau District, Malang Regency. The target of this activity is 100 teenagers in grades 7 and 8. The method applied is the health education method. Health education is carried out by delivering material and asking questions. The success indicator uses a questionnaire measuring tool to measure changes in knowledge in the pre-test and post-test. As a result, the average post-test score in the good knowledge category reached 24%, indicating an increase of 10% that the target teenagers experienced increased knowledge and understanding.